2015
DOI: 10.1111/mve.12112
|View full text |Cite
|
Sign up to set email alerts
|

Rhipicephalus rossicus, a neglected tick at the margin of Europe: a review of its distribution, ecology and medical importance

Abstract: Abstract. Rhipicephalus rossicus (Ixodida: Ixodidae) is a three-host tick with a broad host spectrum that includes wild animals, pets, livestock and humans. Despite its local abundance in certain areas, most of the available information on R. rossicus was published decades ago, mainly by former soviet authors. Its distribution largely overlaps the Eurasian steppe. However, its range may be more extensive than is currently known because this species may have been misidentified as Rhipicephalus sanguineus, princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Recently, the habitat of Rh. rossicus was considerably expanded from the south to the north of Ukraine (Mihalca et al 2015). This study demonstrated that all the examined Rh.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Recently, the habitat of Rh. rossicus was considerably expanded from the south to the north of Ukraine (Mihalca et al 2015). This study demonstrated that all the examined Rh.…”
Section: Discussionsupporting
confidence: 54%
“…This tick species is known to have a vectoral role for only a few pathogens (Francisella tularensis, Crimean-Congo hemorrhagic fever virus, and West Nile virus) and, for most European countries, Rh. rossicus (Jakimov et Kohl-Jakimova, 1911) is considered an alien tick (Mihalca et al 2015). Rh.…”
Section: Discussionmentioning
confidence: 99%
“…Based on cox 1 sequences, R. rossicus was demonstrated to phylogenetically cluster with the eastern Mediterranean Rhipicephalus sp. I, the former having an eastern distribution in Europe, emerging towards the west [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The morphology of ticks was preliminarily assessed using a stereo microscope (SMZ-2 T, Nikon Instruments, Japan, illuminated with model 5000–1, Intralux, Urdorf-Zürich, Switzerland) and standard keys ( R. sanguineus : [14]; R. rossicus : [15]). In the category of R. sanguineus the adanal plate length to breadth ratio (which was reported to provide the only significant difference between Rhipicephalus sp.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the lack of data on SFG Rickettsia in R. rossicus [ 41 ], a tick present in the steppe region of southeastern Romania [ 42 ], R. rossicus collected from owned dogs ( Canis familiaris ) in three locations in Tulcea county were also included in the study. Overall, 128 R. rossicus adults were analysed.…”
Section: Methodsmentioning
confidence: 99%